2020
DOI: 10.26630/jk.v11i3.2221
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Faktor Individu dan Faktor Pekerjaan terhadap Keluhan Musculoskeletal Disorders pada Pegawai

Abstract: Musculoskeletal disorders are work-related diseases and conditions that are not safe and uncomfortable, almost all employees have experienced the disorders, ranging from pain in the neck, shoulders, and lower back. This study was conducted to determine the relationship of individual factors and work factors to complaints of musculoskeletal disorders in employees at the Ministry of Health’s Republic of Indonesia Civil Service Bureau in 2020. This study used a cross-sectional study design with the Purposive Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 3 publications
0
5
0
11
Order By: Relevance
“…Furthermore, statistical analysis showed that there is a significant relationship between age groups and MSDs (Okezue et al, 2020), and this finding is consisstent with the report from the Ministry of Health's Personnel Bureau. A previous study stated that the complaints are more experienced by workers aged > 37 years (Rahayu et al, 2020).…”
Section: Agementioning
confidence: 93%
See 2 more Smart Citations
“…Furthermore, statistical analysis showed that there is a significant relationship between age groups and MSDs (Okezue et al, 2020), and this finding is consisstent with the report from the Ministry of Health's Personnel Bureau. A previous study stated that the complaints are more experienced by workers aged > 37 years (Rahayu et al, 2020).…”
Section: Agementioning
confidence: 93%
“…This finding is also in line with a study at the Indonesian Ministry of Health's Personnel Bureau, where people that sit on chairs that do not conform to anthropometry were more affected. This was because they have a hard texture, wide armrests, and the height of the backrest does not correspond with the body (Rahayu, et al, 2020).…”
Section: Work Facilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pekerja laki-laki dan pekerja perempuan memiliki risiko yang sama untuk terjadinya gangguan MSDs. Sejalan dengan penelitian yang dilakukan oleh Rahayu, dkk (2020) [23] dan penelitian yang dilakukan oleh Sulistyo, dkk (2018). Namun, hasil ini tidak sejalan dengan penelitian yang dilakukan oleh Widianingtyas (2019) yang memaparkan kekuatan otot perempuan dan laki-laki berbeda dengan perbandingan kekuatan otot perempuan 2/3 dari otot laki-laki.…”
Section: Pembahasanunclassified
“…Penelitian terkait isu ini dipandang masih relevan hingga saat ini karena konsekuensinya berakibat pada kerugian besar termasuk pada produktivitas pekerja. Beberapa penelitian terdahulu terkait office work dan postur kerja telah banyak dilakukan baik di berbagai negara (AlOmar et al, 2021;Bagheri & Ghaljahi, 2019;Jusoh & Zahid, 2018;Matos & Arezes, 2015;Rodrigues et al, 2017) termasuk Indonesia (Ahmad & Maesa, 2021;Rahayu et al, 2020;Restuputri et al, 2019;Siboro, 2019). Misalnya, Siboro (2019) mengidentifikasi risiko MSD pada 12 orang pekerja production engineering saat melakukan proses penginputan data menggunakan kuesioner Nordic Body Map (NBM) dan Rapid Office Strain Assessment (ROSA).…”
Section: Pendahuluanunclassified